Oncolytic HSV-IL27 expression improves CD8 T cell function and therapeutic activity in syngeneic glioma models - Alexia K Martin; Uksha Saini; Ilse Hernandez-Aguirre; Yeaseul Kim; Kevin A Cassady; Jack Hedberg; Doyeon Kim; Ravi Dhital (Journal for ImmunoTherapy of Cancer)
Background Malignant gliomas (MGs) are the most common primary brain malignancies and are considered universally fatal. Oncolytic herpes simplex viruses (oHSVs) are promising immunotherapeutics capable of selectively lysing cancer cells, eliciting antitumor immunity, and providing local delivery of immune-activating transgenes. Interleukin 27 (IL-27) is a pleiotropic cytokine capable of enhancing tumor-reactive cytotoxic T lymphocyte (CTL) function while also possessing neuroprotective properties. We hypothesized that IL-27 expression by oHSV would enhance CTL function and improve antiglioma therapeutic activity.Methods We developed an oHSV that expresses IL-27 (C027). The antiglioma efficacy of C027 was tested in three syngeneic orthotopic glioma models derived from both chemical (CT-2A) and genetic (SB28, KR158) glioma lines. Spectral flow cytometry was used to assess immunophenotypic and functional changes in the tumor infiltrates and systemically. To further investigate the C027-related CTL activity, we employed in vivo cell-specific depletion and IL-27 blockade alongside in vitro T cell stimulation assays. Local and systemic antitumor memory was evaluated by both orthotopic and flank tumor rechallenge of C027-treated long-term survivors.Results C027 significantly prolonged survival in syngeneic orthotopic glioma models derived from both chemical (CT-2A) and genetic (KR158, SB28) glioma lines. In the CT-2A model, IL-27-expressing oHSV treatment was associated with increased intratumoral multifunctional effector CTLs and functional T cell populations systemically. Mechanistically, both CD8 T cells and IL-27 were required for the C027 survival benefit in vivo and IL-27 enhanced CTL function in vitro. C027-treated mice that survived their initial tumors had local and systemic antiglioma memory rejecting tumors on rechallenge.Conclusions Our findings demonstrate that IL-27 expression by oHSV significantly improves antiglioma therapeutic efficacy, enhances CTL effector function, and induces durable immune memory. Thus, IL-27-oHSV may provide a promising therapeutic approach for MGs.